Reconstructing Islamic Educational Philosophy to Address Twenty-First Century Global Challenges - M. Aris Akin; Bahaking Rama; Afifuddin Harisah; Hasfiana Hasfiana (IQRO: Journal of Islamic Education, 2026)
Globalization has transformed education through the rapid advancement of digital technologies, artificial intelligence, the Fourth Industrial Revolution, and Society 5.0, while also creating challenges related to moral decline, shifting values, and increasing global competition for human capital. These developments require Islamic education to evolve without compromising the foundational values of the Qur'an and Sunnah. This study examines the global challenges confronting Islamic education, analyzes the relevance of Islamic educational philosophy in addressing these transformations, and proposes strategic directions for its future development. Employing a qualitative library research approach with descriptive analysis, the study reviews relevant scholarly literature. The findings reveal that Islamic educational philosophy remains a robust conceptual foundation for integrating Islamic values with scientific and technological advancement. Accordingly, the development of Islamic education should prioritize an integrated curriculum, continuous professional development for educators, the ethical use of digital technologies, and strengthened character education to cultivate graduates who are adaptive, globally competitive, and morally grounded.